Soil physical and microbiological attributes cultivated with the common bean under two management systems - De Gennaro, Lorena; Souza, Zigomar; Weill, Mara; Souza, Gustavo; Alves, Marlene (Revista Ciência Agronômica, 2014)
Agricultural management systems can alter the physical and biological soil quality, interfering with crop development. The objective of this study was to evaluate the physical and microbiological attributes of a Red Latosol, and its relationship to the biometric parameters of the common bean (Phaseolus vulgaris), irrigated and grown under two management systems (conventional tillage and direct seeding), in Campinas in the state of São Paulo, Brazil. The experimental design was of randomised blocks, with a split-plot arrangement for the management system and soil depth, analysed during the 2006/7 and 2007/8 harvest seasons, with 4 replications. The soil physical and microbiological attributes were evaluated at depths of 0.00-0.05, 0.05-0.10, 0.10-0.20 and 0.20-0.40 m. The following were determined for the crop: density, number of pods per plant, number of beans per pod, thousand seed weight, total weight of the shoots and harvest index. Direct seeding resulted in a lower soil physical quality at a depth of 0.00-0.05 m compared to conventional tillage, while the opposite occurred at a depth of 0.05-0.10 m. The direct seeding showed higher soil biological quality, mainly indicated by the microbial biomass nitrogen, basal respiration and metabolic quotient. The biometric parameters in the bean were higher under the direct seeding compared to conventional tillage.